Performance of Low-Dissipation Euler Fluxes and Preconditioned LU-SGS at Low Speeds (Communications in Computational Physics, 2011)
In low speed flow computations, compressible finite-volume solvers areknown to a) fail to converge in acceptable time and b) reach unphysical solutions.These problems are known to be cured by A) preconditioning on the time-derivativeterm, and B) control of numerical dissipation, respectively. There have been severalmethods of A) and B) proposed separately. However, it is unclear which combinationis the most accurate, robust, and efficient for low speed flows. We carried out acomparative study of several well-known or recently-developed low-dissipation Eulerfluxes coupled with a preconditioned LU-SGS (Lower-Upper Symmetric Gauss-Seidel)implicit time integration scheme to compute steady flows. Through a series of numericalexperiments, accurate, efficient, and robust methods are suggested for low speedflow computations.